Factors Affecting Body Image Discordance Amongst Korean Adults Aged 19–39 Years - Hye-Young Jang; Jung-Won Ahn; Mi-Kyeong Jeon (Osong Public Health and Research Perspectives, 2018)
Objectives This study was designed to investigate factors affecting the discordance between body image and body mass index amongst Korean adults aged 19–39 years. Methods Data (N = 59,361) from the 2014 Korean Community Health Survey was analyzed using descriptive analysis, chi-square test, and logistic regression analysis. Results To examine the factors affecting body image discordance as observed in 43.1% of participants, the group was subdivided into underestimation and overestimation. There were 36.0% of participants that were body image discordant underestimators and 7.1% were overestimators. Multivariate logistic regression analysis showed that the underestimators tended to be men, graduated from high school, married, current/ex-smokers, ex-drinkers, had between 5 to 9 hours sleep (inclusive), had fair to good self-rated health, and demonstrated healthy weight control behavior, relative to the reference group. In comparison, overestimators tended to be in the 19–29 year group and had signs of depression. The OR of individuals who were men, married, and had healthy weight control behavior was significantly lower in the overestimators group. Conclusion These findings show that tailored interventions to promote accurate body awareness should be based on the type of body image discordance. In addition, it is necessary to develop and implement a program of body image improvement that considers the factors affecting body weight discordance.